JIRA 7 essentials : explore the great features of the all-new JIRA 7 to manage projects and effectively handle bugs and software issues /: explore the great features of the all-new JIRA 7 to manage projects and effectively handle bugs and software issues. (2016) - Li, Patrick, 1983-
No abstract available